COMMERCIAL BANKS PROVIDE REMOTE BANKING SERVICES FOREIGN EXPERIENCE AND OPPORTUNITIES TO USE IT IN BANKING PRACTICE OF UZBEKISTAN (American Journal of Interdisciplinary Research and Development, 2023)
Scientific-theoretical views on the provision of remote banking services in commercial banks have been considered. The economic nature and types of remote banking services of commercial banks are presented. The foreign experience of commercial banks providing remote banking services and the possibilities of its use in the banking practice of Uzbekistan were studied.